Los juegos como experiencia de aprendizaje en niños y niñas menores de tres años, del centro infantil del buen vivir “Los Niños Inquietos”, de la parroquia Guanujo, cantón Guaranda, provincia Bolívar; durante el periodo 2011 – 2012. - Carrera Carrera, Daniela (2012)
In our theme children's games as a learning experience in children under 3 years Children's Center of Good Living, Restless Children see that as a major problem there is little importance to incorporate the game as a learning strategy, as not conceived as an opportunity for children to develop their motor aspects, social and emotional. For these reasons, children are shy and timid, almost do not socialize their games that are characterized mimic adult actions such as hunting, fishing, cooking, washing, carrying babies, caring for animals, harvesting, and preparing their own toys; really Educational Center has no financial support or training workshops for promoters for the care of children and especially to develop children's abilities and skills through the fun. We know that games are important for learning and socializing with people around them. It is a challenge and ranging from pre-used material to play with children, develop action proposed, in fact our work is important because we dare game and gain a better stimulate development in areas such as psychomotor, cognitive and social emotional, with the game contributed to the increase of their creative capacities, with the game experience, learn, reflect and actively transform reality, so our job is permanent because of lack of knowledge of the game in the social and emotional development needs to be applied in this Good Children's Center ¨ Children living Restless, we know that do not have plans to improve the problems to solve, in the learning process, because it is a necessity to meet and have fun activities for the development of children. Our theme "GAMES AS A LEARNING EXPERIENCE FOR CHILDREN UNDER THREE YEARS" CHILD CENTER OF GOOD LIVING, RESTLESS CHILDREN OF THE PARISH GUANUJO, GUARANDA CANTON, Bolivar Province, DURING THE PERIOD 2011 - 2012 " is derived for the problem in previous lines, same with foundations investigated by several authors that give reason to implement the game as a learning experience in this children's center of good living ¨ ¨ restless children have no idea what the game helps children to develop. We are happy with the support flanged by Guanujo zone B, the president of the community and the general coordinator, who provided the information, allowed us to observe and analyze the heart to realize that our project is necessary at this school. As a general objective to determine the games as an important factor for the acquisition of learning experiences of children under 3 years, which originates specific objectives. We propose a scenario where we identify the independent and dependent variables, and then operationalize a table showing which allowed us also have questions for the development of the survey. In Chapter I, related to the Theoretical Framework, at this point we recorded topics and subtopics major scientific underpinning our work, pointing out some of them: THE GAME AND EDUCATIONAL GOALS, THE TOYS IN EARLY CHILDHOOD, THE GAME FACTOR THAT PROMOTES LEARNING, LEARNING CONDITIONS THREE LAYERS OF PERSONALIZATION: PSYCHOMOTRICITY, LANGUAGE AND THOUGHT OR HABIT OF REFLECTION. PSYCHOMOTOR, among others. Within this chapter, we present the legal framework, legal provisions that indicate the obligation to educate children, their rights, protections, etc.. We also present the conceptual theory, the terms and key phrases that were used in scientific theory and illustrate clearly the purpose of our work and finally we scored Referential Theory, where we presented the scientific theory behind our work and addition, we place the research institution in the social economic, political, and educational. Chapter of methodological strategies, we present the type of research, methods, techniques, investigated the Universe, the statistical processing. It then presents the analysis and interpretation of results, with the respective tables, graphs and analysis, which led to the formulation, then, conclusions, recommendations and test our hypotheses. Finally, in Chapter IV proposes an alternative to solve such pressing problems through educational games guide which must be applied by the teacher to develop in children psychomotor aspects, social, emotional.